The effect of l-ergothioneine and fetuin on blastocyst development rates - Sakine Ülküm Çizmeci; Dursun Ali Dinç; Mustafa Numan Bucak; Ömer Faruk Yeşilkaya; Vahit Ağır; Maide Gölbaşı; Ayşe Sarı; Hasan Ali Çay (Eurasian Journal of Veterinary Sciences)
Aim: This study, it was aimed to determine the effect of L-ergothionine and Fetuin added to the culture medium on blastocyst development. Materials and Methods: The material of the study consisted of oocytes collected from the ovaries taken from the abattoir. Oocytes, which were incubated for 22 hours in maturation (IVM) medium, were kept in the incubator for 20-22 hours with semen in fertilization (IVF) medium. After the fertilization step, zygotes were transferred in to culture (IVC) drops with antioxidant (Grup 1: L-ergothionine (L-Erg) 0.05 mM (n:100), Grup 2: fetuin 1 mg/ml (n:100), Grup 3: control (n:120)). The 6th and 7th-day blastocysts development were checked. Differences in in vitro embryo production stages were evaluated with the Chi-square test. Results: It was determined that 299 (93.44%) of 320 oocytes were mature. It was determined that the maturation rates of the groups were 94%, 92%, and 94.17%, respectively. It was determined that the cleavage rates were 92.55%, 94.57%, and 92.04%. It was observed that 65 (21.74%) blastocysts were obtained from 299 zygotes taken into the culture stage, and the blastocyst rates in the groups were 45.74%, 11.96%, and 18.58%, respectively. It was determined that the statistical difference between L-ergothionine and the other two groups in blastocyst rates was significant (p<0.05). Conclusion: As a result, L-Erg was seen to improve blastocyst development rates. By investigating the use of L-Erg in different doses, it was thought that the dose can be used with the highest antioxidant activity in vitro embryo production and more blastocysts could be produced.